Music Undergraduates' Usefulness and Importance Expectations: The Bologna Process from an Australian University Perspective - Harvey, Dominic G.; Davidson, Jane W.; Nair, Chenicheri S. (Frontiers in Psychology, 2016)
Abstract The Bologna Process model of higher education has been introduced into some Australian universities since 2008. This model promoted university study through a liberal arts philosophy that advanced a worldview approach at the undergraduate level. The model generalised the student experience and eliminated undergraduate specialisation. An interesting situation for music undergraduate study thus arose. Expertise and expert performance research has argued an opposing educational approach, namely: Extensive long-term commitment through focused practical engagement and specialised tuition as prerequisites to achieving musical mastery, especially in performance. Motivation research has shown that the majority of this specialised development in pre-university years would be accessed and reinforced predominantly through private music tuition. Drawing on this contextual literature, commencing university music undergraduates would have expectations of their prospective study founded from two historical influences. The first: How undergraduates had accessed pre-university music tuition. The second: How and in what ways undergraduates’ pre-university musical activities were experienced and reinforced. Using usefulness and importance measures, the study observed the expectations of students about to commence music undergraduate studies at three representative Australian university music schools. One of these universities operated the Bologna styled model. No other known Australian study has investigated this implementation for any effects upon music undergraduate expectations. How much commencing music undergraduates would draw on their pre-university music instruction and experiences to predict their usefulness and importance expectations formed the basis for this investigation. Strong relationships between usefulness and importance were found across all units of study. Despite strong correlations across all units of study between usefulness and importance, there was a reluctance to be outwardly positive towards units of study that were not practical and performance-related, such as Music History. The educational model did not appear to affect music undergraduate expectations.